The effect of rivaroxaban on myocardial infarction in the ATLAS ACS 2 - TIMI 51 trial. Issue 5 (1st October 2015) - Cavender, Matthew A; Gibson, C Michael; Braunwald, Eugene; Wiviott, Stephen D; Murphy, Sabina A; Toda Kato, Eri; Plotnikov, Alexei N; Amuchástegui, Marcos; Oude Ophuis, Ton; van Hessen, Maarten; Mega, Jessica L
Abstract: Aims: Rivaroxaban reduces cardiovascular death, myocardial infarction (MI), or stroke in patients following acute coronary syndrome (ACS). We aimed to characterize the specific effects of rivaroxaban on the size and type of MI. Methods: The Anti-Xa Therapy to Lower Cardiovascular Events in Addition to Standard Therapy in Subjects with Acute Coronary Syndrome-Thrombolysis in Myocardial Infarction 51 (ATLAS ACS 2-TIMI 51) study randomized 15, 526 patients with a recent ACS to rivaroxaban 2.5 mg BID, rivaroxaban 5 mg BID, or placebo. An independent clinical events committee adjudicated each MI that occurred during the study and further classified them based on type. Data are presented as two-year Kaplan-Meier event rates and hazard ratios (HRs) and 95% confidence intervals (CI). Results: In total, 665 patients experienced a post-randomization MI. The majority ( n =535, 80.5%) were spontaneous (Type 1) events. Rivaroxaban reduced spontaneous MI when compared with placebo (4.4% vs 5.7%, HR 0.80, 95% 0.67–0.95, p =0.01), and there were directionally consistent reductions with both the 2.5 mg BID (4.7% vs 5.7%, HR 0.84, 95% 0.68–1.02, p =0.08) and 5 mg BID doses (4.1% vs 5.7%, HR 0.77, 95% 0.62–0.94, p =0.01) as compared with placebo. Rivaroxaban reduced MI with large elevations in troponin or creatine kinase-MB (CK-MB) fraction (1.8% vs 2.4%, HR 0.73, 95% CI 0.56–0.96, p =0.03) and STEMI events (1.7% vs 2.5%, HR 0.74, 95% CI 0.56–0.99, p =0.04). Conclusions: In patients stabilized and followed after ACS, the majority of MIs that occur are spontaneous and rivaroxaban significantly reduced the incidence of these events. Notably, rivaroxaban reduced MIs with extensive biomarker release and ST-segment elevation.